(untitled) (Research, Society and Development, 2020)
In the search for optimization of production, the use of the ideal plant density is of fundamental importance. So, the objective of this research was to evaluate the effect of planting densities on chive production, varying the spacing between holes and the number of plants per hole. The experimental design was a randomized block design, with twelve treatments in the 4 x 3 factorial scheme, with four spacings between holes (0.05, 0.08, 0.11 and 0.14 m) and three numbers of plants per hole (2, 3 and 4 plants per hole), with four replicates. Leaf number, plant height, leaf diameter, fresh and dry shoot weight (g plant-1) and yield (t ha-1) were evaluated. It was observed that with a greater number of plants per hole, there is reduction in the production per plant, however, the yield is higher. The smaller the spacing, the greater the yield of chives. So it is possible to recommend the higher plant density for chive production, and the use of three or four plants per hole.